Strategi Kepala Desa dalam Meningkatkan Minat Kewirausahaan Bagi Masyarakat di Desa Sukaraja Kecamatan Jerowaru Kabupaten Lombok Timur NTB: Village Head Strategy in Increasing Community Interest in Entrepreneurship in Sukaraja Village, Jerowaru District, East Lombok - Irwan Yon Hadi; Muhammad Makoman Abdul Azis Supriadi (Pendidikan Al-Gafari, 2025)
In facing the era of global competition, the government must be able to prepare qualified and reliable human resources. Preparing qualified and reliable human resources can be done through skills and entrepreneurship training. This study was conducted with the following objectives: 1) To determine the role of the village head in increasing the interest in entrepreneurship in the community in Sukaraja Village, Jerowaru District; 2) To determine the efforts of the Village Head in utilizing village assets as a source of community entrepreneurship in Sukaraja Village, Jerowaru District; and 3) To determine the influence of entrepreneurship on the success of MSMEs in Sukaraja Village, Jerowaru District. In addition, this study was conducted with the aim of identifying effective strategies that can be applied by the village head to stimulate interest in entrepreneurship at the village level. This type of research is descriptive qualitative research. Data collection techniques use observation, interview and documentation methods. The subjects of this study were the Head of Sukaraja Village, the Sukaraja Village Government and the Sukaraja Village Community. The results of this study indicate that the village head can play a key role in increasing interest in entrepreneurship by implementing various strategies, such as providing entrepreneurship training, facilitating access to resources, and forming partnerships with related institutions. In addition, active support in promoting local businesses and developing instructors who support entrepreneurship have also proven effective. This study contributes to further understanding of the role of village heads in supporting entrepreneurship development in Suakraja village, while also providing guidance for village governments in designing more effective policies in increasing community interest and involvement in entrepreneurship.